Effect of SGLT-2 inhibitor, empagliflozin, on blood pressure reduction in Chinese elderly hypertension patients with type 2 diabetes and its possible mechanisms - Lan Cheng; Qianyu Fu; Longhua Zhou; Yuqin Fan; Fenfen Liu; Yuanyuan Fan; Xin Zhang; Weiqing Lin; Xiaohe Wu (Scientific Reports, 2022)
Abstract The current study evaluated the effect of SGLT-2 inhibitor, empagliflozin, on blood pressure reduction in Chinese elderly hypertension patients with type 2 diabetes and investigated its possible mechanisms. 124 patients were randomized to receive 25 mg empagliflozin QD, or placebo double blind for 12 weeks. Patients underwent 24-h ABPM. Endothelial function and arterial stiffness were also measured prior to randomization and at week 12. At week 12, adjusted mean difference versus placebo in change from baseline in mean 24-h SBP was − 8.14 mmHg (95% CI − 10.32, − 3.96, P = 0.005). At week 12, adjusted mean difference versus placebo in change from baseline in mean 24-h DBP was − 5.27 mmHg (95% CI − 8.19, − 1.35, P < 0.001). Changes in office BP were consistent with ABPM. Empagliflozin was well tolerated. Empagliflozin was associated with significant and clinically meaningful reductions in BP versus placebo in Chinese elderly patients with type 2 diabetes and hypertension. The underlying mechanisms possiblely at least in part were the improvements of endothelial function and arterial stiffness associated with empagliflozin. Registration number: ChiCTR2100054678, Registration date: December 23, 2021.